2000
DOI: 10.1007/s11745-000-0638-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of α‐tocopherol and ascorbyl palmitate on the isomerization and decomposition of methyl linoleate hydroperoxides

Abstract: In order to study antioxidant action on lipid hydroperoxide decomposition, the effects of alpha-tocopherol (TOH) and ascorbyl palmitate on the decomposition rate and reaction sequences of 9- and 13-cis,trans methyl linoleate hydroperoxide (cis,trans ML-OOH) decomposition in hexadecane were studied at 40 degrees C. Decomposition of cis,trans ML-OOH as well as the formation and isomeric configuration of methyl linoleate hydroxy and ketodiene compounds were followed by high-performance liquid chromatographic anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1

Year Published

2001
2001
2010
2010

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 20 publications
1
29
1
Order By: Relevance
“…At high concentrations, a-tocopherol inhibits reactions of fatty acid hydroperoxides via peroxyl radicals but does not prevent their conversion to hydroxy-or ketodiene derivatives via alkoxyl radicals (Makinen & Hopia, 2000). By extension, we considered that under such conditions, there should be (i) negligible conversion of PC-LA-OOH 1 to aldehydes 4-7 if they are exclusively formed via peroxyl radical addition and (ii) enhanced relative importance of aldehydes formed via alkoxyl radicals, such as 3.…”
Section: Introductionmentioning
confidence: 99%
“…At high concentrations, a-tocopherol inhibits reactions of fatty acid hydroperoxides via peroxyl radicals but does not prevent their conversion to hydroxy-or ketodiene derivatives via alkoxyl radicals (Makinen & Hopia, 2000). By extension, we considered that under such conditions, there should be (i) negligible conversion of PC-LA-OOH 1 to aldehydes 4-7 if they are exclusively formed via peroxyl radical addition and (ii) enhanced relative importance of aldehydes formed via alkoxyl radicals, such as 3.…”
Section: Introductionmentioning
confidence: 99%
“…Methyl linoleate was oxidized in the dark at 40 °C in the presence of 5% α-tocopherol to produce only cis,trans ML-OOH [8,11]. Cis,trans ML-OOH were purified from non-oxidized ML and α-tocopherol with solid-phase extraction and the purity of the ML-OOH fraction was checked by thin layer chromatography [8].…”
Section: Methodsmentioning
confidence: 99%
“…It has been previously shown that α-tocopherol inhibited the decomposition of methyl linoleate hydroperoxides (ML-OOH) when studied in hexadecane at 40 °C, most likely by acting as a hydrogen atom donor to both peroxyl and alkoxyl radicals [8][9]. Further, α-tocopherol had an effect on the decomposition reaction sequences of ML-OOH, since it inhibited the isomerization of cis,trans to trans,trans ML-OOH and had an effect on the distribution of ML-OOH decomposition products [8]. Koskas et al [10] showed that the addition of α-, γand δ-tocopherols increased the stability of both 13-cis,trans and 13trans,trans hydroperoxides of linoleic acid in an aqueous system.…”
Section: Introductionmentioning
confidence: 99%
“…the presence of antioxidants and metal-ions or other radical forming compounds, phase distribution and presence of amino acids and sugars (Nishiike et al 1999, McClements and Decker 2000, Mäkinen and Hopia 2000. Certain antioxidants slow the decomposition of hydroperoxides, which can reduce the overall rate of lipid oxidation, as the decomposition of hydroperoxides will provide less radicals for the initial H * abstraction from the fatty acid.…”
Section: Vol 13 (2004): 88-99mentioning
confidence: 99%